The rheo-Raman microscope: Simultaneous chemical, conformational, mechanical, and microstructural measures of soft materials - Kotula, Anthony P.; Meyer, Matthew W.; De Vito, Francesca; Plog, Jan; Hight Walker, Angela R.; Migler, Kalman B. (Review of scientific instruments, 2016)
The design and performance of an instrument capable of simultaneous Raman spectroscopy, rheology, and optical microscopy are described. The instrument couples a Raman spectrometer and optical microscope to a rotational rheometer through an optically transparent base, and the resulting simultaneous measurements are particularly advantageous in situations where flow properties vary due to either chemical or conformational changes in molecular structure, such as in crystallization, melting, gelation, or curing processes. Instrument performance is demonstrated on two material systems that show thermal transitions. First, we perform steady state rotational tests, Raman spectroscopy, and polarized reflection microscopy during a melting transition in a cosmetic emulsion. Second, we perform small amplitude oscillatory shear measurements along with Raman spectroscopy and polarized reflection microscopy during crystallization of a high density polyethylene. The instrument can be applied to study structure-property relationships in a variety of soft materials including thermoset resins, liquid crystalline materials, colloidal suspensions undergoing sol-gel processes, and biomacromolecules. Official contribution of the National Institute of Standards and Technology; not subject to copyright in the United States.